2021
DOI: 10.1186/s12866-021-02173-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between aging-dependent gut microbiome dysbiosis and dry eye severity in C57BL/6 male mouse model: a pilot study

Abstract: Background While aging is a potent risk factor of dry eye disease, age-related gut dysbiosis is associated with inflammation and chronic geriatric diseases. Emerging evidence have demonstrated that gut dysbiosis contributes to the pathophysiology or exacerbation of ocular diseases including dry eye disease. However, the relationship between aging-related changes in gut microbiota and dry eye disease has not been elucidated. In this pilot study, we investigated the association between aging-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…Regarding the taxa shown to be positively associated with an increased level of PA/exercise, the Actinobacteria phylum (which contains the genus Bifidobacterium ) has been reported to have positive effects on gut health such as inhibition of pathogens through the modulation of intestinal and immune responses [ 74 ], vitamin production [ 75 ], LPS reduction [ 77 ] and anti-inflammatory properties [ 76 ]. Members of the genus Prevotella are well-known SCFAs producers [ 97 ] and previous studies have found that higher amounts of exercise correlated positively with this genus [ 119 ]. However, there are contrasting results in the literature and some studies have shown that this genus might be associated with inflammation [ 96 ], consequently more research is needed in order to clarify the effects of Prevotella on the gut environment.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the taxa shown to be positively associated with an increased level of PA/exercise, the Actinobacteria phylum (which contains the genus Bifidobacterium ) has been reported to have positive effects on gut health such as inhibition of pathogens through the modulation of intestinal and immune responses [ 74 ], vitamin production [ 75 ], LPS reduction [ 77 ] and anti-inflammatory properties [ 76 ]. Members of the genus Prevotella are well-known SCFAs producers [ 97 ] and previous studies have found that higher amounts of exercise correlated positively with this genus [ 119 ]. However, there are contrasting results in the literature and some studies have shown that this genus might be associated with inflammation [ 96 ], consequently more research is needed in order to clarify the effects of Prevotella on the gut environment.…”
Section: Discussionmentioning
confidence: 99%
“…The increased F/B ratio may have resulted from increased Firmicutes abundance, which was also reflected by the increased abundance of Lachnospiraceae NK4A136 group , which belongs to the phylum Firmicutes, at nighttime. Previous studies showed that the increase of F/B ratio was linked to increases of lipopolysaccharide levels in the plasma and feces of aged male mice [ 25 ], and increased abundance of Cyanobacteria in mice with high F/B ratio can be related to the severity of aging-associated dry eye [ 29 ]. We also observed the increases in F/B ratio and the relative abundance of Cyanobacteria in aged male mice at nighttime.…”
Section: Discussionmentioning
confidence: 99%
“…Balb/c female mice ( n = 54), which were 7 weeks old, were purchased from Orient Bio Inc. (Seongnam, Gyeonggi-do, Korea). The mice cages were in a specific pathogen-free facility at Seoul National University Hospital Biomedical Research Institute, maintained at 22–24 °C with 55% ± 5% relative humidity, and given food and water ad libitum [ 17 ]. The Balb/c mice were assigned to four groups: (1) control (Ct, n = 3 mice), (2) partial trephination group (PT, n = 5 mice), (3) syngeneic (Syn, n = 5 mice), and (4) allogeneic (Allo, n = 5 mice) corneal transplantation group, with one set for each time point ( n = 18 mice/week).…”
Section: Methodsmentioning
confidence: 99%